1977
DOI: 10.1115/1.3439211
|View full text |Cite
|
Sign up to set email alerts
|

Sensing of Drill Wear and Prediction of Drill Life

Abstract: High-speed steel drill life is found to be a strong function of the work material hardness (Tl α HB−16) when drilling cast iron. This strong dependence may account for the large variation in the life of the drills, which is observed in industrial conditions. Torque, thrust, and power are observed to be functions of drill wear. In the drilling of cast iron using H.S.S. drills of 10.32 mm (13/32 in.) dia at 690 rpm or 22.25 M/min (73 ft/min) maximum, the following relations were observed: torque(M)=0.125HBd2f+0.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
37
0

Year Published

1986
1986
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 92 publications
(37 citation statements)
references
References 0 publications
0
37
0
Order By: Relevance
“…The simultaneous monitoring of thrust force and torque is rather common (see e.g. [2,6,[11][12][13][14][15][16][17][18][19]) and special electronics have been developed for this purpose [11].…”
Section: Torque Drift Force and Feed Forcementioning
confidence: 99%
See 3 more Smart Citations
“…The simultaneous monitoring of thrust force and torque is rather common (see e.g. [2,6,[11][12][13][14][15][16][17][18][19]) and special electronics have been developed for this purpose [11].…”
Section: Torque Drift Force and Feed Forcementioning
confidence: 99%
“…Based on the tests with copper alloy and a model described in [19], formulas that define the thrust force and torque as a function of feed per revolution, drill diameter and flank wear have been developed and their applicability has also been tested [6]. It should be noted that the tests indicated that the increase in cutting speed over the range studied had no significant effect on work material strength, and hence it has no significant effect on cutting forces [6].…”
Section: Torque Drift Force and Feed Forcementioning
confidence: 99%
See 2 more Smart Citations
“…The obtained average thrust force P av during peck drilling with the 0.1 mm drill shown in Fig. 11(a) rapidly increases in the early stage and then gradually increases at almost a constant rate with the increase in the number of drilled holes (8) . The characteristics of the average thrust force with the increase in the number of drilled holes is expected to be similar to the characteristics of the width of the flank wear land of the main cutting edge at the outer corner shown in Fig.…”
Section: Burr Occurring At the Outlet Of A Drilled Holementioning
confidence: 99%